Pengembangan Smart Modul Tema 8 ”Manusia dan Lingkungan“ Untuk Kelas V Sekolah Dasar - Octavia Tri Anggraini; Erwin Putera Permana; Farida Nurlaila Zunaidah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is backgrounded by the results of observations obtained, namely the use of learning media used by teachers is predominantly monotonous and makes students feel saturated or bored to learn. With these problems, researchers develop smart module teaching materials to assist teachers in providing material to students so that students can understand the material well. This study aims to (1) find out the validity of the development of human module smart teaching materials and the environment, (2) know the practicality of human module smart teaching materials and the environment for class V elementary schools and, (3) know the effectiveness of the smart module teaching materials "Humans and the Environment". The development model used is the ADDIE model. The development of smart module teaching materials has met the criteria of validity, practicality and, effectiveness by concluding that teaching materials are very well used without improvement through the results of the questionnaire of the validity of teaching material experts with a score of 86% and material with a score of 83%. The practicality results obtained a questionnaire of 90% teacher response and 92% student response.